Efek Kadmium terhadap profil DNA Bacillus cereus ATCC 9632 dan Pseudomonas aeruginosa WT pada Limbah Sintetik Elektroplating - Sholikah, Umi; Trihadiningrum, Yulinah (LPPM ITK, 2018)
The electroplating industry produces wastewater containing heavy metals. The high surface area of bacteria has the potency to reduce heavy metals content in wastewater since it has ability to absorb the metals. This study aims to find out the bacterial DNA profile after Cd bioremoval process using Bacillus cereus 9632 and Pseudomonas aeruginosa WT. Bacterial culture is applied in synthetic electroplating wastewater. Some Cd concentrations are used to perform Range Finding Test by bacterial culture. The study was conducted in a batch system for three days. The viability test was done by measuring the value of Optical Density and Total Plate Count, while bacterial DNA profile was analyzed by using electrophoresis. The cell viability of B.cereus ATCC 9632 and P.aeruginosa WT had the same pattern which is the higher concentration of Cd metals on cell bacteria surface, the lower cell bacteria viability. The DNA of the control bacteria has the difference between the size and number of bands.